Changing prevalence of some selected gastrointestinal diseases vis-à-vis H. pylori infection - Fixa, Bohumil; Komárková, Olga; Nozicka, Zdenek (Hepato-gastroenterology, 2011)
BACKGROUND/AIMS: The aim of this prospective study was to evaluate the changing relative prevalence of peptic ulcer disease, gastroesophageal reflux disease and functional dyspepsia over 18 years (four periods) in a country with a significant decline of H. pylori prevalence. METHODOLOGY: In total, 3000 patients were studied. Only the first 750 consecutive dyspeptic patients in each period who were referred to endoscopy and in whom the abovementioned diseases were diagnosed were assessed. In each patient, H. pylori status was evaluated. RESULTS: From 1988 to 2006, the number of peptic ulcer disease patients decreased significantly while that of reflux esophagitis patients significantly increased. Prevalence of functional disease patients continued to be high. The prevalence of H. pylori in gastroesophageal reflux disease and functional dyspepsia patients declined significantly. CONCLUSIONS: The results show remarkable changes in the epidemiology of peptic ulcer disease and reflux esophagitis among the population with a decrease of H. pylori prevalence. The significant decrease of H. pylori among functional dyspepsia patients, which continues to have a high prevalence, indirectly supports the opinion that the role of H. pylori is of no dominant importance in this disease. The decline of peptic ulcer disease is partially explainable by the decrease of H. pylori infection in the general population, but other factors should be established.
Keywords: gastroezofageální reflux; Humans; lidé středního věku; prevalence; Gastroesophageal Reflux; Aged; dospělí; Dyspepsia; senioři; lidé; dyspepsie; peptický vřed; Adult; Helicobacter Infections; Peptic Ulcer; Helicobacter pylori; Middle Aged; Adolescent; Czech Republic; Aged, 80 and over; Prevalence; senioři nad 80 let; Česká republika; prospektivní studie; infekce vyvolané Helicobacter pylori; mladiství; Prospective Studies